Simulation of fixed bed reactor for iron catalyzed fisher-tropsch reactor using MATLAB - Sarwat Hameed (NUST2012-60738-MCES-64112F); Shahid Hussain Ansari (USPCAS-E, NUST, Islamabad, 2014)
TH-10
Keywords: MS-ESE Thesis MS Thesis